(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The dominant feature of modern research methodology is its empiricism as an inability to go beyond the limits of the visible and the measurable things. This its property contradicts with the basic definition of the truth of knowledge according to Aristotle. Therefore, the purpose of the proposed article is to expand the whole range of methodological opportunities of the basic definition of truth and return to the completeness first of the problem formulation, and then of its solution.